Vitamin MK‐7 enhances vitamin D3‐induced osteogenesis in hMSCs: modulation of key effectors in mineralization and vascularization. (29th October 2012) - Gigante, A.; Brugè, F.; Cecconi, S.; Manzotti, S.; Littarru, G. P.; Tiano, L.
Abstract The osteoblast is the bone‐forming cell and is derived from mesenchymal stem cells (MSCs). Osteo‐inductive substances could represent a useful therapeutic approach during the fracture repair process. The aim of this work was to evaluate the effects of vitamin MK‐7, alone or in association with vitamin D3, in differentiating human MSCs (hMSCs) in vitro along the osteoblastic lineage. In particular, primary endpoints of the study include gene and protein markers of osteoblast differentiation. Considering genes involved in bone formation and mineralization, our data show that vitamin MK‐7 enhances vitamin D3 gene induction of osteocalcin (OC). Among genes related to cell growth and differentiation, a specific effect of vitamin MK‐7 was observed for growth differentiation factor‐10 (GDF10) and insulin‐like growth factor 1 (IGF1), the latter being also involved in the induction of vascular endothelial growth factors (VEGFA). Accordingly, vitamin co‐supplementation greatly affected VEGFA and its receptor fms‐related tyrosine kinase 1 (FLT1), a key factor in both angiogenic and osteogenic processes. These results stress the relevance of MK‐7 and D3 co‐supplementation in the bone‐healing process as able to modulate the expression of genes involved in both mineralization and angiogenesis. Moreover, at the protein level co‐association of vitamins might provide an optimal balance between induction and carboxylation of osteocalcin, essential for its functionality in the extracellular matrix (ECM). Our results may provide hints for therapeutic application of hMSCs in bone disease, clarifying mechanisms involved in stem cell‐mediated bone development, and they also highlight the relevance of co‐supplementation strategies, since single supplementations might result in a suboptimal effect. Copyright © 2012 John Wiley & Sons, Ltd.